2004
DOI: 10.1063/1.1637341
|View full text |Cite
|
Sign up to set email alerts
|

State-to-state rotational rate constants for CO+He: Infrared double resonance measurements and simulation of the data using the SAPT theoretical potential energy surface

Abstract: An extensive data set of 54 time-resolved pump-probe measurements was used to examine COϩHe rotational energy transfer within the CO vϭ2 rotational manifold. Rotational levels in the range J i ϭ2 -9 were excited and collisional energy transfer of population to the levels J f ϭ1 -10 was monitored. The resulting data set was analyzed by fitting to numerical solutions of the master equation. State-to-state rate constant matrices were generated using fitting law functions and ab initio theoretical calculations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…3. Finally, the ratio Q 2 /Q 0 % 0.5 obtained here is comparable to what is obtained for collisions of CO with He (typically 0.2, see [14,15]) and CO 2 with He (typically 0.4, see [16,17]). …”
Section: R (1) Manifold and Qsupporting
confidence: 74%
“…3. Finally, the ratio Q 2 /Q 0 % 0.5 obtained here is comparable to what is obtained for collisions of CO with He (typically 0.2, see [14,15]) and CO 2 with He (typically 0.4, see [16,17]). …”
Section: R (1) Manifold and Qsupporting
confidence: 74%
“…They compared their experimental data with results from two high-quality potential energy surfaces, with the ab initio SAPT surface of Heijmen et al, and with the XC­(fit) surface of LeRoy et al and found better agreement for the SAPT surface . Lorenz et al measured state-to-state differential cross sections for rotational excitation of CO in collision with Ne at a collision energy near 511 cm –1 , and they have compared their experimental data with results based on the CCSD­(T) surface of McBane and Cybulski and the surface of Moszynski et al In 2004, Smith et al reported state-to-state rotational transition rate constants for CO–He obtained from infrared double resonance measurements and scattering calculations based on the SAPT potential of Heijmen et al Their work provided a nice demonstration of the quality of the SAPT potential. Even better ab initio CO–He potentials were calculated more recently and tested against experimental data in scattering calculations by Peterson and McBane .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our recent experiments to measure rotationally inelastic rates for ground-state CN radicals by saturation recovery kinetics revealed a large, systematic variation in the signal recovery rates as a function of the Doppler detuning. The observations may seem at first surprising, since, unlike the earlier reports of initial Doppler selection and subsequent translational thermalization, the transient bleaching of our probed rotational states is performed without Doppler selection, yet the Doppler spectrum of the depletion, or “hole”, shows rapid translational cooling in the initial stages of the return to equilibrium. This report characterizes the Doppler-resolved kinetics measured under these conditions, and the inelastic and elastic collisions that account for these effects.…”
Section: Introductionmentioning
confidence: 63%
“…6,7 The use of a Doppler shift for velocity selection to study velocity-dependent reaction cross sections has been applied to rotational energy transfer (RET) in excited states, 8,9 and in Doppler-resolved double-resonance methods, 10−12 where corrections for Doppler selection are commonly applied in careful kinetic studies of energy transfer. 11,13,14 The competition among optical excitation, velocity-changing collisions, and inelastic collisions plays a central role in a substantial body of classic work on collisional effects in sub-Doppler saturation spectroscopy and speed-dependent collisional broadening. 8,15−19 Observations similar to those in the present report have been noted in the context of inelastic and depolarizing collisions of the A state of CN in the laboratory of Costen and McKendrick.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation